Fine Mapping of Prostate Cancer Aggressiveness Loci on Chromosome 7q22-35 - Liu, Xin (2010)
BACKGROUND: Deciphering the genetic basis of prostate cancer aggressiveness could provide valuable information for the screening and treatment of this common but complex disease. We previously detected linkage between a broad region on chromosome 7q22-35 and Gleason score—a strong predictor of prostate cancer aggressiveness. To further clarify this finding and focus on the potentially causative gene, we undertook a fine-mapping study across the 7q22-35 region. METHODS: Our study population encompassed 698 siblings diagnosed with prostate cancer. 3,072 single nucleotide polymorphisms (SNPs) spanning the chromosome 7q22-35 region were genotyped using the Illumina GoldenGate assay. The impact of SNPs on Gleason scores were evaluated using affected sibling pair linkage and family-based association tests. RESULTS: We confirmed the previous linkage signal and narrowed the 7q22-35 prostate cancer aggressiveness locus to a 370 kb region. Centered under the linkage peak is the gene KLRG2 (killer cell lectin-like receptor subfamily G, member 2). Association tests indicated that the potentially functional non-synonymous SNP rs17160911 in KLRG2 was significantly associated with Gleason score (p = 0.0007). CONCLUSIONS: These findings suggest that genetic variants in the gene KLRG2 may affect Gleason score at diagnosis and hence the aggressiveness of prostate cancer.